The Embedded Health Management Academic: A Boundary Spanning Role for Enabling Knowledge Translation Comment on "CIHR Health System Impact Fellows: Reflections on ‘Driving Change’ Within the Health System" - Eljiz, Kathy; Greenfield, David; Taylor, Robyn (International journal of health policy and management, 2020)
Healthcare organisations are looking at strategies and activities to improve patient outcomes, beyond clinical interventions. Increasingly, health organisations are investing significant resources in leadership, management and team work training to optimise professional collaboration, shared decision-making and, by extension, high quality services. Embedded clinical academics are a norm in, and considered a strength of, healthcare organisations and universities. Their role contributes, formally and informally, to clinical teaching, knowledge sharing and research. An equivalent, but significantly less common role, addressing the management of healthcare organisations, is the embedded health management academic (EHMA). A stimulus encouraging this intertwined embedded academic role, in both clinical and managerial fields, is the demand for the translation of knowledge between academic and industry contexts. In this essay, we describe the EHMA role, its value, impact and potential for enabling healthcare organisation improvement. Focusing on the business of healthcare, the EHMA is a conduit between sectors, stakeholders and activities, enabling different organisations and experts to co-create, share and embed knowledge. The value and impact achieved is significant and ongoing, through the nurturing of an evidence-based management culture that promotes ongoing continuous improvement and research activities.